Shaping global teacher identity in a short-term mobility programme. Issue 1 (1st January 2017) - Tangen, Donna; Henderson, Deborah; Alford, Jennifer; Hepple, Erika; Alwi, Amyzar; Abu Hassan Shaari, Zaira; Alwi, Aliza
ABSTRACT: This article explores the shaping of Australian and Malaysian pre-service teachers' possible selves in a short-term mobility programme. With the theory of possible selves, individuals imagine who they will become based on their past and current selves. The focus of the research was on pre-service teachers' possible selves as global and culturally responsive teachers. The experiential learning through participation in the programme allowed participants to consider their future possible selves as teachers with a deeper understanding of diverse learners' needs and how they might strive to address these needs in their own classrooms. The scaffolding of reflections in the programme encouraged the pre-service teachers to take on multiple perspectives, to step outside their comfort zones and in many ways to see the world from different eyes. The research found that through experiential learning in the short-term mobility programme both the Australian and Malaysian pre-service teachers gained in positioning their cultural selves currently and as future teachers, suggesting that there is merit in utilising the theory of possible selves in future research in the area of shaping teacher identity.